Minority positions in the German Council of Economic Experts: A political economic analysis - Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
I investigate minority votes in the German Council of Economic Experts. The dataset contains information on the voting behavior of the council members over the period 19712011. The results show that the best predictor of minority voting is being nominated by the trade unions: a council member nominated by the trade unions isabout 70 percentage points more likely to vote against the majority opinion of the German Council of Economic Experts. This voting pattern indicates that the channel of political appointment influences voting behavior.
Keywords: D72; 330; Decision making in committees; minority voting; policy preferences; German Council of Economic Experts